2011
DOI: 10.1093/erae/jbr063
|View full text |Cite
|
Sign up to set email alerts
|

Stop or go? How is the UK food industry responding to front-of-pack nutrition labels?

Abstract: Food nutrition labels have been used for over a decade to aid consumers in making more informed diet choices and to potentially reduce societal costs from diet-related diseases and health conditions. While there is some evidence of the effectiveness of nutrition labels in changing consumption patterns, the scale of such improvements have been marginal. This has led certain government agencies to consider alternative forms of nutrition information. One such approach is front-of-pack (FOP) nutrition labels which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…Nevertheless, our findings suggest that food manufacturers may choose not to display the HSR on nutritionally inferior products, aiming to prevent discouraging consumers from purchasing their product. These findings are consistent with prior reports that indicate that voluntary implementation of FOPL generally results in inconsistent uptake of labelling systems (14)(15)(16) . To ensure that consumers are provided with consistent information across product ranges to make informed food choices, making HSR labelling a mandatory requirement should be considered.…”
Section: Health Star Rating On Packaging and Pricesupporting
confidence: 92%
“…Nevertheless, our findings suggest that food manufacturers may choose not to display the HSR on nutritionally inferior products, aiming to prevent discouraging consumers from purchasing their product. These findings are consistent with prior reports that indicate that voluntary implementation of FOPL generally results in inconsistent uptake of labelling systems (14)(15)(16) . To ensure that consumers are provided with consistent information across product ranges to make informed food choices, making HSR labelling a mandatory requirement should be considered.…”
Section: Health Star Rating On Packaging and Pricesupporting
confidence: 92%
“…Public information efforts have nudged the food industry to make notable improvements, such as removal of trans fat from many products. Other improvements, such as reducing the sodium content in prepared foods, could have important public health effects and public-private efforts, such as the U.S. National Salt Reduction Initiative (New York City, 2010) and the United Kingdom sodium reduction campaign (van Camp, Hooker, & de Souza Monteiro, 2010;van Camp, de Souza Monteiro, & Hooker, 2011), could play an important role in incentivizing such changes.…”
Section: Ongoing Challenges and Research Implicationsmentioning
confidence: 99%
“…These additional labels can also support already existing labels on nutrition information (Nutrition Facts Panel) in that they lower the cognitive burden of decision making (e.g., Zhu, Lopez, & Liu, 2016). Also, it is in line with van Camp et al (2012), who stress that the food industry can use labels to provide specific information about food products to target consumer groups and drive demand for their products. Based upon our evidence, there is an opportunity for food manufacturers to increase the demand for their healthy foods among parents with children who are overweight or obese.…”
Section: Resultsmentioning
confidence: 72%
“…Previous research focusing on strategies and marketing efforts to improve adult consumer dietary choices has shown that front-of-package (FOP) nutrition information (e.g., trafficlight labels) and health claims can influence purchasing habits (Sacks, Rayner, & Swinhurn, 2009;van Camp, D'Souza Monteiro, & Hooker, 2012;Wansink, 2003;2004). As well, research has shown that simple front-of-package logos such as the "Pick the Tick" developed by the National Heart Foundation can affect consumer food choices and producer food formulations (Mueller & Umberger, 2010;Williams, McMahon, & Boustead, 2003;Young & Swinburn, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation